2020
DOI: 10.3389/fneur.2020.01009
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Optical Coherence Tomography Angiography in Cerebral Small Vessel Disease, Ischemic Stroke, and Dementia: A Systematic Review

Abstract: Objective: To investigate the application of optical coherence tomography angiography (OCTA) in cerebral small vessel disease (SVD), ischemic stroke and dementia. Methods: We conducted a systematic search in MEDLINE (from inception) and EMBASE (from 1980) to end 2019 for human studies that measured retinal parameters in cerebral SVD, ischemic stroke, and dementia using OCTA. Results: Fourteen articles ( n = 989) provided relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Moreover, cAMP/AC independent mechanisms have also been found to be involved in the α2-AR-mediated vasoconstriction. For example, α2-AR can induce the vasoconstriction in the porcine palmar lateral vein via the activation of ERK-dependent signaling pathway and Src tyrosine kinases [ 75 ]. Interestingly, compared to nondemented, low pathology control subjects, AD patients showed a significant increase of α2A-AR activity.…”
Section: Adrenergic Mechanisms Underlying Aβ/tau-cerebrovascular Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cAMP/AC independent mechanisms have also been found to be involved in the α2-AR-mediated vasoconstriction. For example, α2-AR can induce the vasoconstriction in the porcine palmar lateral vein via the activation of ERK-dependent signaling pathway and Src tyrosine kinases [ 75 ]. Interestingly, compared to nondemented, low pathology control subjects, AD patients showed a significant increase of α2A-AR activity.…”
Section: Adrenergic Mechanisms Underlying Aβ/tau-cerebrovascular Interactionsmentioning
confidence: 99%
“…Worth noting, one study in 2019, found that retinal vasculature did not discriminate AD patients from healthy controls [ 100 ]. However, much more recent experimental data were reported to support the utility of retinal vascular changes as potential marker of AD [ 75 , 101 104 ].…”
Section: Clinical Implications Of Cerebrovascular Abnormality On Ad Early Diagnosis and Therapymentioning
confidence: 99%
“…It is responsible for the blood supply to the outer retina which includes the retinal pigment epithelium (RPE) and photoreceptors, and some portions of the inner retina (McLeod and Lutty, 1994). OCTA has been reported to be a convenient and invasive method to screen and monitor dementia development (Zhang et al, 2020). Our current study used an in-built software in the OCTA tool to assess the choriocapillaris blood flow in EOD patients which helps the reduction of projection artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…The retinal and cerebral small vessels share similar embryologic origins, anatomical features, and physiological properties; therefore, the retinal vessels may serve as a research model to detect subclinical cerebrovascular changes associated with FD [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%